2015
DOI: 10.5603/ep.2015.0006
|View full text |Cite
|
Sign up to set email alerts
|

Powszechny niedobór witaminy D u dorosłych z województwa pomorskiego po miesiącach niskiego i wysokiego promieniowania UVB

Abstract: Introduction: Widespread vitamin D deficiency has been reported worldwide and evidence of its deleterious effects on health has been accumulating. There is insufficient data concerning vitamin D status among the Polish adult population. The aim of the study was to determine vitamin D status and factors influencing it -UVB exposure, supplementation, and diet -among adults in northern Poland following months of low and high natural UVB radiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…Although the beneficial effect of vitamin D on human health is already well established, vitamin D deficiencies have become a global problem (Holick, 2006;Hosseinnezhad & Holick, 2013). Recent studies conducted in Poland also underlined this issue (Kmieć et al, 2014;Pludowski et al, 2014, Kmieć et al, 2015. Furthermore, seasonal changes in vitamin D level that were observed, pointed out the necessity of its proper supplementation, especially in the winter season (Pludowski et al, 2013, Kmieć et al, 2015.…”
Section: Introductionmentioning
confidence: 92%
“…Although the beneficial effect of vitamin D on human health is already well established, vitamin D deficiencies have become a global problem (Holick, 2006;Hosseinnezhad & Holick, 2013). Recent studies conducted in Poland also underlined this issue (Kmieć et al, 2014;Pludowski et al, 2014, Kmieć et al, 2015. Furthermore, seasonal changes in vitamin D level that were observed, pointed out the necessity of its proper supplementation, especially in the winter season (Pludowski et al, 2013, Kmieć et al, 2015.…”
Section: Introductionmentioning
confidence: 92%
“…The Institute of Medicine supports the key role of calcium and vitamin D in the maintenance of skeletal health and recommended a daily intake of 1.2 g of calcium and 800 IU of vitamin D for women in older age [5]. In Poland, 90% of people have insufficiency of vitamin D [23,24,38].…”
Section: Rycina 4 Zmiany Stężenia Całkowitej Witaminy D W Grupie 2 Pmentioning
confidence: 99%
“…In Europe, the mean serum 25(OH)D levels, reported in population-based studies, vary from 18 ng/mL (29 nmol/L) in Italy to 30 ng/mL (75 nmol/L) in Norway [20]. It has been observed that more than 40% of U.S. and European men and women, and more than 50% of postmenopausal women, are affected by vitamin D deficiency [7,21], including Poland, where it is found in approximately 90% of the general population [22][23][24]. In some populations, the deficit is ever stronger, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Vitamin D deficiency has been shown to be prevalent in Northern Poland [6], and summer sun exposure was not sufficient to fully eliminate it [7,8]. Furthermore, vitamin D deficiency was stated in up to 90% of Poland's adult population [9].…”
Section: Introductionmentioning
confidence: 99%